2017
DOI: 10.5115/acb.2017.50.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of petrous and cavernous parts of internal carotid artery

Abstract: The petrous and cavernous parts of internal carotid artery (ICA) are obscure and are not readily accessible to observation/imaging. These parts have broad biological and medical interest because of their peculiar shape. Given the their clinical importance and the scarce data available based mostly on imaging, the present study was aimed at studying these parts of ICA by dissection. The study was carried out on 56 ICAs obtained from embalmed adult cadavers and 10 ICAs from five fetuses. The foetal ICAs were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
5
13
0
Order By: Relevance
“…The present data partially confirm the existing literature. In fact, length and diameter of the horizontal portion are similar to those reported on cadavers and CT-scans 6,10,16,19,20 ; on the other hand, angles of the posterior and anterior genu are higher than the intervals reported by Vijaywargiya et al 22 . However, the previous study was performed on embalmed cadavers, and the encountered discordances may be due to the elastic deformation of ICA during the measurement procedures.…”
Section: Comparison With Literaturesupporting
confidence: 83%
See 2 more Smart Citations
“…The present data partially confirm the existing literature. In fact, length and diameter of the horizontal portion are similar to those reported on cadavers and CT-scans 6,10,16,19,20 ; on the other hand, angles of the posterior and anterior genu are higher than the intervals reported by Vijaywargiya et al 22 . However, the previous study was performed on embalmed cadavers, and the encountered discordances may be due to the elastic deformation of ICA during the measurement procedures.…”
Section: Comparison With Literaturesupporting
confidence: 83%
“…Even less data are available for what concerns the angles of posterior and anterior genu: a recent study first found that both the angles were positively correlated to each other, and negatively correlated with the length of the horizontal portion of IPCA. On average, the posterior and anterior genu ranged between 31° and 110°, and between 68° and 124°, respectively 22 .…”
Section: Comparison With Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The cavernous part of the internal carotid artery (ICA) is in the form of a siphon that is twisted and torqued in three dimensions. 1 It is the most medial structure within the cavernous sinus, so it leans directly against the lateral surface of the body of the sphenoid bone, where bone can be absent in 4% of cases or a very thin space (< 1 mm) can be seen in 66%. 2 Prevalence of intracranial saccular aneurysms varies in the literature, from 0.4% to 6%, with a preponderance in female patients (92%).…”
Section: Introductionmentioning
confidence: 99%
“…After traversing through cavernous sinus it curves up medial to anterior clinoid process. Finally, the artery emerges through dural roof of cavernous sinus [5] .…”
Section: Introductionmentioning
confidence: 99%